Strategi Keunggulan Kompetitif Vilo Gelato: Analisis Kualitatif Menciptakan Diferensiasi Dalam Industri Gelato - Tania Athaliav; Novita Novita (Value: Jurnal Manajemen dan Akuntansi, 2025)
The Indonesian culinary industry, notably that of ice cream and gelato, has undergone substantial transformation, becoming an integral component of the nation's lifestyle.Gelato, a type of ice cream renowned for its dense texture and rich flavour, provides a more gratifying culinary experience in comparison to conventional ice cream.There has been a steady increase in public interest in gelato, as demonstrated by the proliferation of gelato outlets in various locations.This trend presents a lucrative business opportunity for gelato in Indonesia. Vilo Gelato, established in 2017 by Jennike Veronika and her partner, has garnered consumer attention by offering over 60 premium gelato flavours tailored to local palates.This research aims to explore the competitive advantage strategies of PT. Vilo Kreasi Rasa (Vilo Gelato) in the gelato industry.The study employs a qualitative method with a case study approach, and data analysis is conducted using NVivo 15 software. The findings indicate that the competitive advantage of Vilo Gelato is rooted in its unique product offerings and the distinctive ambiance of its retail outlets. The company's outlets are distinguished by their unique designs and themes, which serve as significant attractions for consumers. Furthermore, Vilo Gelato places a premium on product quality, undertaking consistent innovation to introduce new and appealing flavours.